Fabrication of electrospun nanofibers made of watermelon peel extract and PVA and investigating their antioxidant and antibacterial activities - Soliman, Wafaa (AUC Knowledge Fountain, 2019)
Food waste has become a huge problem globally since thousands of different food items are wasted all over the world which affects our environment severely due to the emissions of greenhouse gas due to anaerobic decomposition and leakage at the garbage. Fruit wastes like the peels and seeds are a major contribution to the waste products thrown everyday especially in juice industries. The antioxidant and antimicrobial activities of food wastes have been of great interest nowadays due to oxidative stress and antibiotic resistance problems. However the stability of the fruits or vegetables wastes was a challenge to perform these activities under controlled release and remains stable for long period of time. Therefore, the purpose of this study is to extract watermelon peel using different solvents and examines its total phenolic content using Folin & Ciocalteu's method. The best solvent showed the highest TPC was methanol and selected for the tests below. The watermelon peel extract (WPE) was mixed with polyvinyl alcohol (PVA) and used to fabricate nanofibers (WPE/PVA). To the best of our knowledge WPE/PVA nanofibers have never been reported before. The main motivation behind this fabrication process is to enhance the antioxidant and antibacterial activities of WPE and more importantly is to effectively use such fruit waste at nanoscale that gives the WPE higher stability and controlled release that reached 72 hours. After successful preparation of WPE/PVA nanofibers several parameters were carefully controlled such as applied voltage, solution flow rate, and distance from the needle to the collector and needle diameter. The WPE/PVA nanofibers were fabricated at different concentrations 0.1%, 0.5%, 1% and 2.5% of the PVA weight. All the concentrations showed 100% ± 5 entrapment efficiency. The antioxidant and antibacterial activities were effectively enhanced in WPE/PVA nanofibers where the IC50 of the WPE/PVA nanofibers was 0.12 mg/mL while the IC50 of the WPE alone was 0.55 mg/mL so the activity was increased approximately 22% in the WPE/PVA nanofibers. While in the antibacterial activity the WPE/PVA nanofibers showed 83.5 ± 0.9% inhibition of the E.coli, however it showed in the WPE 70.3 ± 4.2% inhibition of the E.coli therefore the WPE/PVA nanofibers is 1.2 folds higher activity that WPE. While for S. aureus the WPE/PVA nanofibers showed 94 ± 0.8% inhibition, however it showed in the WPE 83.5 ± 1.12% inhibition of the therefore, the WPE/PVA nanofibers is 1.12 folds higher activity than that of WPE. The PVA fibers (unloaded) showed no significant inhibition activity in both E.coli and S. aureus. Characterization of the waste content like phenolics, FTIR, SEM... etc before and after Nano-formulation were done.